(untitled) - Wyatt, Rawdon (London, 2008)
his workbook provides a resource for students studying towards the TOEFL (Test of English as a Foreign Language) exam, which is an entry requirement for non-native speakers at more than 6000 universities worldwide.
Keywords: Tiếng Anh,Test of English as a foreign language,English language,Kiểm tra tiếng Anh như một ngôn ngữ nước ngoài; Kỳ thi,Study guides,Examinations,Hướng dẫn học